SENIOR HIGH SCHOOL STUDENTS’ ABILITY IN ANSWERING READING COMPREHENSION QUESTIONS OF HIGHER ORDER THINKING SKILLS - Eka Pradana; Indra Hartoyo (Universitas Negeri Medan, 2023)
This study aims to describe the ability of tenth-grade students of SMA Swasta Imelda Medan in answering reading comprehension question of Higher Order Thinking Skills based on Curriculum 2013 with essay question of Narrative Text legend story. This research was conducted with Quantitative-Descriptive method. The data analysis was a test that consist of 3 analysing level question, 2 evaluating level question and 1 creating level question. Total 6 essay HOTS question with the text was Narrative Text legend story. The test was taken from 30 students of class X-MIPA SMA Swasta Imelda Medan. This research has found that the ability of the tenth-grade students of SMA Swasta Imelda Medan was poor. With the mean of Analysing 49.07; Evaluating 51.25; and Creating 28.3. The number of students who got excellent in analysing were 8 students, evaluating has 10 students and creating only has good category with 2 students. From this research, students should improve their creative and critical thinking. And teachers also need to take more attention to guide the students.keywords: Ability, HOTS, Reading Comprehension, and Narrative Text